Phytochemical and Pharmacological Review of Arcangelisia flava (L.) Merr: Insights into Its Bioactive Compounds and Therapeutic Potential - Yabansabra, Yuliana Rut; Bowaire, Anike; Simaremare, Eva S.; Yaam, Demas R.; Tiris, Aira; Nadeak, Erpina S.M. (Jurnal Biologi Papua, 2025)
Arcangelisia flava (L.) Merr., commonly known as kayu kuning, is a medicinal plant traditionally used in Southeast Asian medicine. Various studies have identified bioactive compounds such as furanoditerpenes, alkaloids, flavonoids, tannins, and phenolic compounds that contribute to its pharmacological activities, including antimicrobial, antioxidant, and antidiabetic effects. Despite the growing body of research on its pharmacological potential, the mechanisms of action of these bioactive constituents remain inadequately understood, and clinical evidence supporting its use in modern therapy is still limited. This systematic review compiles data from diverse scientific sources, focusing on the phytochemical composition, extraction methods, pharmacological activities, and comparisons with conventional pharmaceutical agents. The analysis revealed that A. flava contains various bioactive constituents responsible for its therapeutic effects. Furanoditerpenes demonstrate antimicrobial and antifungal activity, while alkaloids and phenolic compounds exhibit significant antioxidant and antidiabetic properties. Extraction techniques varied across studies, affecting the efficiency of bioactive compound isolation. Comparisons with standard pharmaceuticals suggest that A. flava extracts exhibit comparable efficacy in several pharmacological domains. These findings indicate that A. flava holds considerable promise as a natural therapeutic agent. However, further investigations are needed to clarify its pharmacological mechanisms through pharmacokinetic and pharmacodynamic studies, as well as clinical trials to confirm its safety and effectiveness in human applications. The integration of modern technological approaches such as metabolomics and bioinformatics could facilitate the identification, standardization, and development of phytopharmaceutical products derived from A. flava, thereby advancing its potential use in evidence-based medicine.